Exploring the effectiveness of 3-chloro-4-morpholin-4-yl-1,2,5-thiadiazole as an eco-friendly corrosion inhibitor for mild steel in HCl solution: Experimental and DFT analysis - Ahmed Al-Amiery; Nadia A. Betti; Lina M. Shaker (Results in Engineering)
Corrosion is a significant issue in many industries, particularly where metals are exposed to harsh chemical environments. This study investigates the efficacy of 3-Chloro-4-morpholin-4-yl-1,2,5-thiadiazole (CMTD) as a corrosion inhibitor for mild steel in 1 M HCl solution across a temperature range of 303–333 K. Using weight loss measurements, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization techniques, the inhibition efficiency of CMTD was evaluated at different concentrations and temperatures. The results show that CMTD achieves a maximum inhibition efficiency of 96.8 % at a highest inhibitor concentration, even at elevated temperatures. The adsorption of CMTD on the mild steel surface follows the Langmuir adsorption isotherm, with a calculated free energy of adsorption (ΔGads) of −39.5 kJ mol−1, confirming a spontaneous chemisorption process. Quantum chemical Density Functional Theory (DFT) studies further elucidated the relationship between CMTD's molecular structure and its inhibition efficiency. Key parameters, including the energy gap (Egap = 3.551 eV), highest occupied molecular orbital (EHOMO = −6.317 eV), and lowest unoccupied molecular orbital (ELUMO = −2.766eV), were calculated to understand CMTD's reactivity. Additionally, global reactivity descriptors such as chemical hardness (η), electronegativity (χ), and the electron fraction transferred (ΔN) from CMTD to the iron surface were analyzed. These findings suggest that CMTD is highly effective in preventing corrosion and can be applied in industries where mild steel is exposed to acidic environments, such as in petrochemical and industrial cleaning processes.